ANALISIS PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA PERIMBANGAN DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH DI KOTA BATAM - Anita, Dewi; Efriyenti, Dian (SCIENTIA JOURNAL, 2026)
This study aims to analyze the effect of Local Own-Source Revenue (PAD), Balancing Funds, and Capital Expenditure on the financial performance of the Batam City Government. This research is motivated by fluctuations in PAD and Balancing Funds, as well as a decline in the proportion of Capital Expenditure during the 2017–2024 period, which indicates the need for an evaluation of regional fiscal performance. The study employs a quantitative approach using secondary data obtained from the Budget Realization Reports of the Batam City Government. Data were analyzed using multiple linear regression supported by classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results show that PAD and Capital Expenditure have a positive and significant effect on regional financial performance, while Balancing Funds have a negative and significant effect, indicating a high level of dependence on central government transfers. Simultaneously, PAD, Balancing Funds, and Capital Expenditure significantly affect the financial performance of the Batam City Government